2023
DOI: 10.1038/s41467-023-36312-7
|View full text |Cite
|
Sign up to set email alerts
|

Isoform- and ligand-specific modulation of the adhesion GPCR ADGRL3/Latrophilin3 by a synthetic binder

Abstract: Adhesion G protein-coupled receptors (aGPCRs) are cell-surface proteins with large extracellular regions that bind to multiple ligands to regulate key biological functions including neurodevelopment and organogenesis. Modulating a single function of a specific aGPCR isoform while affecting no other function and no other receptor is not trivial. Here, we engineered an antibody, termed LK30, that binds to the extracellular region of the aGPCR ADGRL3, and specifically acts as an agonist for ADGRL3 but not for its… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 84 publications
0
17
0
Order By: Relevance
“…Since our initial efforts to find a tethered agonist mutant with impaired G protein signaling that retained normal autoproteolytic cleavage were unsuccessful, we designed a construct that rendered Lphn2 resistant to autoproteolytic cleavage but preserved tethered agonist activity. Previous studies showed that replacing threonine-838 in the tethered agonist of Lphn1 or threonine-923 in the tethered agonist of Lphn3 to glycine inhibited autoproteolysis while maintaining proper folding of the receptor ( Araç et al, 2012 ; Kordon et al, 2023 ). Thus, we mutated the analogous threonine-829 in Lphn2 (Lphn2_T829G) and confirmed that Lphn2_T829G was cleavage resistant using immunoblotting ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…Since our initial efforts to find a tethered agonist mutant with impaired G protein signaling that retained normal autoproteolytic cleavage were unsuccessful, we designed a construct that rendered Lphn2 resistant to autoproteolytic cleavage but preserved tethered agonist activity. Previous studies showed that replacing threonine-838 in the tethered agonist of Lphn1 or threonine-923 in the tethered agonist of Lphn3 to glycine inhibited autoproteolysis while maintaining proper folding of the receptor ( Araç et al, 2012 ; Kordon et al, 2023 ). Thus, we mutated the analogous threonine-829 in Lphn2 (Lphn2_T829G) and confirmed that Lphn2_T829G was cleavage resistant using immunoblotting ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…The cells are then mixed, and extent of aggregation is imaged and quantified. 73 WT mCELSR1 was able to efficiently induce aggregation (Figure 5B, C) whereas the ΔCADH1-8 construct was defective in aggregation and the ΔCADH9-GAIN construct was able to form aggregates but not as efficiently as WT. In the cell-cell junction enrichment assay, full length protein is expressed using HEK293T cells observed in groups, and the localization of mCELSR1 is compared to ZO-1, a cell-cell junction marker.…”
Section: The Cadherin Repeat Module Of Cadh1-8 Is Essential For the A...mentioning
confidence: 99%
“…To aid the cryo-EM structural analysis of ADGRL3, we screened a synthetic antibody binder (sAB) library to obtain binders specific to the HormR/GAIN domains of ADGRL3. A biotinylated fragment of the ADGLR3 ECR containing HormR and GAIN domains was used as input for generation of highaffinity sABs against ADGRL3 by phage display selection using a diverse synthetic phage library based on a humanized antibody Fab scaffold [56][57][58] , and four rounds of selection were performed as described previously 35 . Following the selection and initial validation, we identified 10 unique HormR/GAIN binders by a single-point phage enzyme-linked immunosorbent assay (ELISA) (Supplementary Fig.…”
Section: Gain Domain Of Adgrl3mentioning
confidence: 99%
“…Binding of synthetic ligands to the ECR of ADGRL3 and other aGPCRs can alter receptor signaling 28,35,36,68,69 . We tested the effect of sABs LK3 and LK1 binding on ADGRL3 signaling activity using an SRE-luciferase assay 24 .…”
Section: Synthetic Antibodies Can Activate Adgrl3 and Alter The Confo...mentioning
confidence: 99%
See 1 more Smart Citation